2001
DOI: 10.1093/carcin/22.11.1837
|View full text |Cite
|
Sign up to set email alerts
|

Lack of promotion of 7,12-dimethylbenz[a]anthracene-initiated mouse skin carcinogenesis by 1.5 GHz electromagnetic near fields

Abstract: The effects of 1.5 GHz electromagnetic near fields of time division multiple access (TDMA) signal for the Personal Digital Cellular, Japanese cellular telephone standard (PDC) used for cellular phones, on mouse skin carcinogenesis initiated by 7,12-dimethylbenz[a]anthracene (DMBA) were examined. Ten-week-old ICR female mice were treated with a single application of DMBA on shaved dorsal skin by painting at a concentration of 100 microg/100 microl acetone per mouse. One week later, mice were divided into four g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Experimental evidence from animal and laboratory studies at the cellular level confirms the lack of genotoxic effect of RFs (Krewski et al 2001; Moulder et al 1999). Similarly, an investigation in rodents did not find support for the suggestion that growth of tumors induced by other agents may be promoted by RFs from mobile phone signals (Imaida et al 2001; Mason et al 2001). …”
Section: Mechanismsmentioning
confidence: 89%
“…Experimental evidence from animal and laboratory studies at the cellular level confirms the lack of genotoxic effect of RFs (Krewski et al 2001; Moulder et al 1999). Similarly, an investigation in rodents did not find support for the suggestion that growth of tumors induced by other agents may be promoted by RFs from mobile phone signals (Imaida et al 2001; Mason et al 2001). …”
Section: Mechanismsmentioning
confidence: 89%
“…The most perplexing questions are those concerned with the problems of whether such an exposure either triggers or promotes disease processes. A few well-controlled human studies failed to show a positive association between exposure to RF radiation and carcinogenesis [Imaida et al, 2001;Bartsch et al, 2002], in vivo studies of chronic exposure of animals to repeated high and low level RF irradiation indicate a positive relationship between exposure and carcinogenesis [Rapacholi, 1997;Moulder et al, 1999]. The majority of the studies of long-term exposure indicate a negative impact on overall health, and suggest the possibility that RF radiation may have epigenetic activity, particularly at high exposure levels [Brusick et al, 1998;Verschaeve and Maes, 1998;Moulder et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…Previously we conducted similar tumor initiationpromotion experiments to clarify whether EMF had a tumor enhancement effect on rat liver or mouse skin carcinogenesis [Imaida et al, 1998[Imaida et al, , 2000[Imaida et al, , 2001 and concluded that continuous local exposure did not have a tumor promoting activity. Furthermore, recent work in our laboratory with Big Blue mice demonstrated that local exposure to 900 MHz EMF did not cause mutations in mouse brain [Takahashi et al, 2002].…”
Section: Discussionmentioning
confidence: 99%